Studi Kualitatif: Identifikasi Determinan Audit Report Lag Pada Kantor Akuntan Publik DSI Cabang Surabaya - Umi Nur Fryda Kusli Rochmah; Acynthia Ayu Wilasittha (JRAK: Journal of Accounting Research and Computerized Accounting, 2024)
Abstract This study utilizes a qualitative approach to identify determinants and prevention of report lag audit incidents at the CPA Firm (KAP) DSI Surabaya Branch. Audit report lag refers to the era between the end of accounting and the date of provision of the audit report as an important indicator of the efficiency and effectiveness of the audit process. Interviews to the auditors at KAP Djoko, Sidik & Indra Surabaya Branch who are experienced in handling audit report lag cases are the primary data sources for this study. The study reveals the main factors influencing audit report lag through in-depth interviews with auditors and managers at the KAP DSI Surabaya Branch. The study's results indicate that auditor capacity and workload, client complexity, audit planning and scheduling, and client coordination are the main determinants contributing to audit report lag. Based on these findings, there are several practical suggestions can be carried out by auditors to minimize audit report lag, such as optimizing workload distribution, improving audit planning and scheduling, ongoing training programs, and improving communication and coordination with clients. Keywords: Audit Report Lag; Audit Quality; and Public Accounting Firm